2009
DOI: 10.1159/000255578
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Tolerability of Donepezil, Rivastigmine and Galantamine for Patients with Alzheimer’s Disease: Systematic Review of the ‘Real-World’ Evidence

Abstract: Background/Aims: The purpose of this systematic review was to compare the safety and tolerability of the cholinesterase inhibitors (ChEIs) donepezil, rivastigmine and galantamine for treating mild to moderate Alzheimer’s disease (AD) patients in routine clinical practice. Methods: Electronic databases (Cochrane Library, Medline, EMBASE; accessed October 2008) and manual bibliographic searches were conducted to identify head-to-head non-randomised studies examining ChEIs for the treatment of AD. Data were extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
55
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(65 citation statements)
references
References 66 publications
5
55
0
2
Order By: Relevance
“…Interestingly, in our study most of the mixed dementia patients had subcortical vascular disease. These and other studies 4,7,9,27,28 reported higher rates of nausea and vomiting in GAL treated participants, compared with placebo, consistent with our results and the generally favorable safety profile observed in previous studies in AD disease 5,25,26,29 . A systematic review 3 of 15 trials evaluating the efficacy of NIM in AD, CVD and mixed dementia found benefits of the NIM therapy on short-term outcomes of global and cognitive function, when results were pooled together, despite dementia specific etiology.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Interestingly, in our study most of the mixed dementia patients had subcortical vascular disease. These and other studies 4,7,9,27,28 reported higher rates of nausea and vomiting in GAL treated participants, compared with placebo, consistent with our results and the generally favorable safety profile observed in previous studies in AD disease 5,25,26,29 . A systematic review 3 of 15 trials evaluating the efficacy of NIM in AD, CVD and mixed dementia found benefits of the NIM therapy on short-term outcomes of global and cognitive function, when results were pooled together, despite dementia specific etiology.…”
Section: Discussionsupporting
confidence: 92%
“…GAL has been tested in several randomized clinical trials for AD 3,16,25,26 and has been also evaluated in a systematic review, which examined its efficacy and safety for patients with vascular cognitive impairment, but also included studies enrolling mixed dementia patients 4 . Two studies were deemed eligible for the systematic review (GAL-INT-26 and GAL-INT-6), the first assessing a population with probable vascular dementia 27 and the other, a mixed population of vascular dementia and AD with simultaneous CVD patients 9,28 .…”
Section: Discussionmentioning
confidence: 99%
“…The fact that both of these drugs are readily available in many countries for clinical use now offers the potential for improved efficacy over prucalopride alone and improved cardiovascular and bronchial safety over the use of physostigmine. Thus, when compared with neostigmine, donepezil is safer to use, especially in the elderly (Birks, 2006;Lockhart et al, 2009) who are more likely to suffer from acute colonic pseudo-obstruction (Hyatt, 1987). Further, prucalopride has been shown to have no cardiac safety liability in elderly patients treated for constipation (Camilleri et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Perception of bitterness by the gustatory system helps to identify toxic or spoiled foods that should not be ingested; however, many nonharmful compounds also are perceived as bitter, including some artificial sweeteners and many medicines (23)(24)(25)(26)(27)(28)(29)(30). Tastant receptors have also been identified outside the gustatory system, including bitter receptors in ciliated epithelial airway and enteroendocrine cells (31)(32)(33)(34), but their function in these tissues is still being determined.…”
mentioning
confidence: 99%